2013
DOI: 10.1007/s40266-013-0088-6
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib in Very Elderly Patients with Chronic Myeloid Leukemia in Chronic Phase: A Retrospective Study

Abstract: Results from this large cohort of patients show that no upper age limit should be applied for the administration of imatinib to patients with chronic-phase CML; the very elderly, including those with concomitant severe diseases, should be offered this treatment. The role of a reduced starting dose of imatinib warrants further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 21 publications
3
20
0
Order By: Relevance
“…However, several older patients actually receive a starting dose of imatinib < 400 mg/day, i.e. lower than the standard dose, owing to worse performance status compared to younger ones [15]. …”
Section: Discussionmentioning
confidence: 99%
“…However, several older patients actually receive a starting dose of imatinib < 400 mg/day, i.e. lower than the standard dose, owing to worse performance status compared to younger ones [15]. …”
Section: Discussionmentioning
confidence: 99%
“…P450 inhibitors decrease the metabolism of TKI and may enhance their complications. The Italian study10 demonstrated that the achievement of complete cytogenetic response was similar in individuals 75 and older and younger individuals. However a major molecular response was rarer.…”
Section: Age and Pharmacology Of Tkimentioning
confidence: 97%
“…While it is still possible that age-associated immune dysfunctions or age-related changes in hematopoietic stroma may lead to a more aggressive disease, at present there is no conclusive evidence that the biology of CML changes with age. As older patients appear to benefit from TKI to the same extent as the young1,910 one may conclude that age-related biological differences do not seem to impact the prognosis of CML in the elderly.…”
Section: Biology Of CML and Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…This information is critical, given the rapid development of new oral antineoplastic agents during the past two decades. Data limited to imatinib [ 29 ] and oral idarubicin [ 30 ] suggest that the absorption of oral agents is unaffected by age. These studies included only elderly in good general conditions and under 85.…”
Section: Pharmacology Of Agingmentioning
confidence: 99%